Boosting Work Ethic through Human Relations in Indonesia: Meningkatkan Etos Kerja melalui Hubungan Kemanusiaan di Indonesia - Debora Martina; Vera Firdaus (Academia Open, 2024)
This study explores the impact of human relations and work discipline on the work ethic of employees at PT. Parastar Distrindo. Using a quantitative approach, data were collected via questionnaires and surveys from 120 office employees. Analysis with SPSS version 22 revealed that both human relations and work discipline positively and significantly influence work ethic. The study highlights the importance of strong interpersonal relationships and strict adherence to work rules in fostering a productive work environment. Recommendations include enhancing human relations and work discipline practices to boost employee work ethic and further research on additional influencing factors. Highlight: Human relations and work discipline enhance employee work ethic. Quantitative analysis via SPSS highlights interpersonal relationships and rule adherence. Improve human relations; explore additional factors impacting work ethic. Keywoard: Human relations, work discipline, work ethic, quantitative analysis, PT. Parastar Distrindo